Targeting Accuracy of the Subthalamic Nucleus in Deep Brain Stimulation Surgery: Comparison Between 3 T T2-Weighted Magnetic Resonance Imaging and Microelectrode Recording Results. Issue 1 (2nd August 2017) - Nowacki, Andreas; Debove, Ines; Fiechter, Michael; Rossi, Frédéric; Oertel, Markus Florian; Wiest, Roland; Schüpbach, Michael; Pollo, Claudio
Abstract: BACKGROUND: Targeting accuracy in deep brain stimulation (DBS) surgery can be defined as the level of accordance between selected and anatomic real target reflected by characteristic electrophysiological results of microelectrode recording (MER). OBJECTIVE: To determine the correspondence between the preoperative predicted target based on modern 3-T magnetic resonance imaging (MRI) and intraoperative MER results separately on the initial and consecutive second side of surgery. METHODS: Retrospective cohort study of 86 trajectories of DBS electrodes implanted into the subthalamic nucleus (STN) of patients with Parkinson's disease. The entrance point of the electrode into the STN and the length of the electrode trajectory crossing the STN were determined by intraoperative MER findings and 3 T T2-weighted magnetic resonance images with 1-mm slice thickness. RESULTS: Average difference between MRI- and MER-based trajectory lengths crossing the STN was 0.28 ± 1.02 mm (95% CI: −0.51 to −0.05 mm). There was a statistically significant difference between the MRI- and MER-based entry points on the initial and second side of surgery ( P = .04). Forty-three percent of the patients had a difference of more than ±1 mm of the MRI-based-predicted and the MER-based-determined entry points into the STN with values ranging from −3.0 to + 4.5 mm. CONCLUSION: STN MRI-based targeting is accurate in the majority of cases on the first and second side of surgery. In 43% of implanted electrodes, we found a relevant deviation of more than 1 mm, supporting the concept of MER as an important tool to guide and optimize targeting and electrode placement.